Recurrent Syncope, a Clue in Amyloid Cardiomyopathy - Julian A. Marin-Acevedo; Catalina Sanchez-Alvarez; Ali A. Alsaad; Ricardo J. Pagán (Case Reports in Medicine)
Infiltrative cardiomyopathies include a variety of disorders that lead to myocardial thickening resulting in a constellation of clinical manifestations and eventually heart failure that could be the first clue to reach the diagnosis. Among the more described infiltrative diseases of the heart is amyloid cardiomyopathy. The disease usually presents with subtle, nonspecific symptoms. Herein, we illustrate a case of recurrent syncope as the initial presenting symptom for systemic amyloid with polyneuropathy and cardiomyopathy as a cause of syncope. The article illustrates the role of advanced cardiac imaging in the diagnosis of the disease with a focused literature review. We also highlight the role of early, shared decision-making between patient, family, and medical team in the management of cardiac amyloidosis.